Coping With a Mass Casualty: Insights into a Hospital's Emergency Response and Adaptations After the Formosa Fun Coast Dust Explosion. (23rd August 2020) - Chuang, Sheuwen; Woods, David D.; Ting, Hsien-Wei; Cook, Richard I.; Hsu, Jiin-Chyr
ABSTRACT: Objective: The study provides a comprehensive insight into how an initial receiving hospital without adequate capacity adapted to coping with a mass casualty incident after the Formosa Fun Coast Dust Explosion (FFCDE). Methods: Data collection was via in-depth interviews with 11 key participants. This was combined with information from medical records of FFCDE patients and admission logs from the emergency department (ED) to build a detailed timeline of patients flow and ED workload changes. Process tracing analysis focused on how the ED and other units adapted to coping with the difficulties created by the patient surge. Results: The hospital treated 30 victims with 36.3% average total body surface area burn for over 5 hours alongside 35 non-FFCDE patients. Overwhelming demand resulted in the saturation of ED space and intensive care unit beds, exhaustion of critical materials, and near-saturation of clinicians. The hospital reconfigured human and physical resources differently from conventional drills. Graphical timelines illustrate anticipatory or reactive adaptations. The hospital's ability to adapt was based on anticipation during uncertainty and coordination across roles and units to keep pace with varying demands. Conclusion: Adapting to beyond-surge capacity incident is essential to effective disaster response. Building organizational support for effective adaptation is critical for disaster planning.